PENDUGAAN EROSI TANAH PADA LAHAN BEKAS TAMBANG BATU BINTANG SUB DAS BATANG KALULUTAN DAN SUNGAI IPUH KABUPATEN PADANG PARIAMAN - Adrinal Adrinal; Utri Luki; Pedri Kasman (Jurnal Solum, 2008)
An erosion prediction using Universal Soil Loss Equation (USLE) was conducted from August 2006 to February 2007.  The research was aimed to predict amount of soil erosion and erosion risk rate of ex-obsidian mining of Kalulutan and Ipuh River, Padang Pariaman District.  The result showed that the highest soil erosion was predicted under ex-obsidian mining (45% slope) namely 2.593 t/ha/y and the lowest was found under mixed farm (3-8% slope), 4,95 t/ha/y. Erosion risk rate of ex-obsidian mining was very heavy whilst for mixed farm varied from light to very heavy.   Keyword: erosion prediction, ex-obsidian mining, Sub-catchments area